2018
DOI: 10.1161/strokeaha.117.019929
|View full text |Cite
|
Sign up to set email alerts
|

Shared and Distinct Rupture Discriminants of Small and Large Intracranial Aneurysms

Abstract: Small (<5 mm) and large (≥5 mm) IAs have different hemodynamic and clinical, but not morphological, rupture discriminants. Size-dichotomized rupture discrimination models performed better than the aggregate model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 33 publications
0
41
0
Order By: Relevance
“…For instance, aneurysm size remains a major criterion for treatment as it is assumed that large IAs are at higher risk for rupture than small IAs. However, small IAs with regular shape may also rupture . Therefore, it has been suggested that growing aneurysms independently of their size are more likely to rupture .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, aneurysm size remains a major criterion for treatment as it is assumed that large IAs are at higher risk for rupture than small IAs. However, small IAs with regular shape may also rupture . Therefore, it has been suggested that growing aneurysms independently of their size are more likely to rupture .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, more factors signifying the biological processes leading to growth and rupture should be considered for decisions onto treatment of unruptured IAs. Indeed, there is increasing evidence showing that hemodynamic forces exerted on the vessel wall by the flowing blood may induce vascular remodelling leading to IA formation, growth and rupture . Hemodynamic forces may thus be considered as additional prediction factors for IA outcome .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These algorithms have been successfully used in AI studies. 11,12 Compared with traditional ML algorithms, DL uses an artificial neural network that extracts features from images automatically to create its own filters, called feature maps (independent of human input) and memorizes visual patterns with highest frequency. There are convolution layers, pooling layers, fully connected layers, and normalization layers; the pooling reduces the number of parameters and reduces overfitting.…”
Section: Brief Overview Of Aimentioning
confidence: 99%